(untitled) (Jóvenes en la Ciencia, 2024)
There is research where it is mentioned that there are a large number of studies focused on the effects of weaning carried out incorrectly for the infant, but there are few that focus on the effects on the mother’s health, whether physical, mental or emotional. Weaning is understood as "weaning the infant or offspring from suckling animals, seeking nutrition by other means". It is a process that takes time and must be carried out in an adequate manner, since it is a moment that marks this affective bond already established so that negative consequences do not occur in the mother, such as high levels of depression, anxiety and stress. The objective of the research was to analyze the levels of anxiety generated by the weaning process in women. Quantitative, retrospective and cross-sectional research where the selection of participants was at convenience, the "IDARE" questionnaire was applied, which measures anxiety levels in 2 scales. The results showed that mothers experienced higher levels of anxiety when they led the weaning process compared to when weaning was guided by the baby. Specifically, a higher percentage of mothers reported moderate (30%) to high (25%) anxiety in mother-led weaning, whereas a higher percentage (25%) experienced lower levels of anxiety in infant-led weaning. These findings highlight the importance of considering both the weaning approach and the individual characteristics of mothers when providing support during this transitional stage. In addition, personal factors, such as low income and being a first-time mother, were identified that may increase anxiety during this process. It was concluded that the type of weaning, either mother-led or baby-led, significantly influences the levels of anxiety experienced by mothers, being higher in mother-led weaning.